Depot-Specific Adipose Tissue Metabolite Profiles and Corresponding Changes Following Aerobic Exercise - Brennan, Andrea M.; Tchernof, Andre; Gerszten, Robert E.; Cowan, Theresa E.; Ross, Robert (Frontiers in Endocrinology, 2018)
Objectives: Total, visceral and abdominal subcutaneous adipose tissue (AT) depots have distinct associations with cardiometabolic health; however, the metabolite profiles that characterize each AT depot and its reduction following exercise are poorly understood. Our objectives were to (1) assess the independent associations between identified metabolites and total, visceral and abdominal subcutaneous AT; and (2) examine whether changes in metabolite concentrations and AT mass following aerobic exercise are associated. Methods: A secondary analysis was performed in 103 middle-aged abdominally obese men and women ([mean (SD)], 52.4 (8.0) years) randomized into one of four groups varying in exercise amount and intensity for 6 months duration: high amount high intensity, high amount low intensity, low amount low intensity, and control. 147 metabolites were profiled by liquid chromatography-tandem mass spectrometry. AT mass was measured by magnetic resonance imaging. Results: Individual metabolite associations with AT depots confirmed several established cross-sectional relationships between the obesity phenotype and metabolic pathways. Collapsed across exercise groups, reduction in visceral AT predicted increases in pyroglutamic acid (B=-0.41) and TCA cycle intermediates (succinic (B=-0.41) and fumaric acid (B=-0.20)), independent of change in total AT. Changes in UDP-GlcNAc (B=0.43), pyroglutamic acid (B=-0.35), histidine (B=0.20), citric acid/isocitric acid (B=-0.20), and creatine (B=0.27) were significantly associated with changes in total AT (false discovery rate = 0.1). Conclusions: Our findings point to potential biomarkers of depot-specific AT reduction that may play a direct role in mediating cardiometabolic improvements.